Design and develop an active mixer extruder for ink based 3D printer - Cheah, Choon Kit (2022)
Nowadays, 3D printing is essential for manufacturing micro-scale materials. Direct Ink Writing (DIW) is the most versatile form of additive manufacturing for producing microscale materials with ink formulations. The ink formulation for DIW exhibits a shear-thinning behaviour when deposited through the nozzle tip. Most DIW commercial printers cannot print soft materials with specific properties uniformly. So, the project focus will be on designing and developing an active mixer to blend two viscous silicone ink formulations into a homogeneous solution. In order to demonstrate the active mixer performance, a prototype was fabricated in the workshop, which consists of a dc motor, mixing chamber, motor housing, and rotating impeller. Then, both experimental and CFD fluid modelling with Ansys Fluent are carried out to evaluate the prototype performance in silicone mixing. When the impeller isn't rotating, there isn't any applied shear rate at the silicone that produces a heterogeneous ink profile. During 12 rpm rotation, the impeller applies a shear rate to the silicone that promotes mixing due to lower viscosity. As the impeller speed increases from 12 to 24 rpm, the fluid viscosity reduces from 93.72 to 81.11 Pa.s which improves the mixing rate. Overall, it takes 2 s and 1 s to achieve a steady mixing state for the prototype performance. At 24 rpm speed, the active mixer can reduce the pressure of non-Newtonian mixing, which increases the fluid residence time. So, the output produced can be more homogeneous at 28,000 Pa, unlike 0 rpm and 12 rpm where the pressure fluctuates. Lastly, different blue silicone ink inlet velocities are simulated at 1mm/s, 3mm/s, and 5mm/s to determine the output material composition without changing the impeller and red silicone ink flow rate. Lastly, it was found that the red ink volume fraction will decrease at the output as more blue silicone ink flows into the mixing chamber. For the contribution, the design can help save raw material and energy costs and expand business opportunities to develop new products.